Strategies for developing 3D printed ovarian model for restoring fertility - Ramya Nair; Meghana Kasturi; Vidhi Mathur; Raviraja N. Seetharam; Kirthanashri S Vasanthan (Wiley, 2024)
Abstract Ovaries play a crucial role in the regulation of numerous essential processes that occur within the intricate framework of female physiology. They are entrusted with the responsibility of both generating a new life and orchestrating a delicate hormonal symphony. Understanding their functioning is crucial for gaining insight into the complexities of reproduction, health, and fertility. In addition, ovaries secrete hormones that are crucial for both secondary sexual characteristics and the maintenance of overall health. A three‐dimensional (3D) prosthetic ovary has the potential to restore ovarian function and preserve fertility in younger females who have undergone ovariectomies or are afflicted with ovarian malfunction. Clinical studies have not yet commenced, and the production of 3D ovarian tissue for human implantation is still in the research phase. The main challenges faced while creating a 3D ovary for in vivo implantation include sustenance of ovarian follicles, achieving vascular infiltration into the host tissue, and restoring hormone circulation. The complex ovarian microenvironment that is compartmentalized and rigid makes the biomimicking of the 3D ovary challenging in terms of biomaterial selection and bioink composition. The successful restoration of these properties in animal models has led to expectations for the development of human ovaries for implantation. This review article summarizes and evaluates the optimal 3D models of ovarian structures and their safety and efficacy concerns to provide concrete suggestions for future research.